Design and fabricate a go-kart back suspension system - Mohd Bakeri, Muhammad Syafiq (2025)
This project aims to create a go-kart rear suspension system that enhances safety, handling, and ride comfort. The primary difficulty lies in selecting the appropriate suspension type, such as independent suspension or solid axle suspension, while striking the correct balance between weight, adjustability, and chassis fit. The project's goal is to increase grip and stability, particularly on uneven tracks and at high speeds. The method entails studying existing suspension designs, concentrating on important elements like balance and weight distribution, and creating a system that adds little weight, is simple to modify, and fits the go-kart frame perfectly. Prototypes will be tested in real-world settings to make adjustments, and computer simulations will forecast the suspension's performance. Making use of cutting-edge technology, such as lightweight materials with electrical controls for in-the-moment modifications, will aid in performance optimization. Safety is a top priority, so make sure the components are robust and have contingency plans in case they fail